Three new leafhopper species of Macropsis Lewis (Hemiptera: Cicadellidae: Eurymelinae: Macropsini) with a key to species from the Indian subcontinent - Viraktamath, C.a.; Yeshwanth, H.m. (Zootaxa, 2021)
Three new species, Macropsis dalhousiensis sp. nov. (India: Himachal Pradesh), M. krishna sp. nov. (India: Karnataka) and M. puttarudriahi sp. nov. (India: Arunachal Pradesh) are described and illustrated. M. krishna breeds on Acacia catechu and is actively attended by the ant Camponotus sp. in nymphal and adult stages. A checklist and a revised illustrated key to species of the genus for the Indian subcontinent are also given.